2019
DOI: 10.4103/jrms.jrms_879_16
|View full text |Cite
|
Sign up to set email alerts
|

Conversion to resectability using transcatheter arterial chemoembolization alternating with mFOLFOX6 in patients with colorectal liver metastases

Abstract: Background:Colorectal cancer is one of the most common malignancies in the world, and about 25% of colorectal cancer patients present with colorectal cancer liver metastases (CRCLM) even at new diagnosis. The study was to evaluate the safety and efficacy of transcatheter arterial chemoembolization (TACE) alternating with mFOLFOX6 in Chinese patients with unresectable CRCLM.Materials and Methods:In this study, by combining the systemic and regional treatment, the resectability rate, overall survival, and progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Approximately 35% of patients with colorectal cancer have metastases confned to the liver alone and become the ultimate cause of death in approximately 50% of these patients [7,8]. Studies have reported that when colorectal cancer patients develop liver metastases, only 10-20% of patients can be treated with radical surgery [9], and their 5-year survival rate is around 35-55% [10]. However, in patients with unresectable CRLMs, the 5-year survival rate is less than 5%.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 35% of patients with colorectal cancer have metastases confned to the liver alone and become the ultimate cause of death in approximately 50% of these patients [7,8]. Studies have reported that when colorectal cancer patients develop liver metastases, only 10-20% of patients can be treated with radical surgery [9], and their 5-year survival rate is around 35-55% [10]. However, in patients with unresectable CRLMs, the 5-year survival rate is less than 5%.…”
Section: Introductionmentioning
confidence: 99%